Le tropicalisme social, des géographies engagées et le « hub » brésilien - Federico Ferretti (Revue d’Histoire des Sciences Humaines)
This paper explores the contributions of authors who worked in the first Brazilian universities—the Universidade de São Paulo, founded in 1934, and the Universidade do Distrito Federal, founded in 1935—and became internationally influential, by focusing on their acquaintance with European (and especially French) colleagues who contributed to the “University Missions” in Brazil. These scholars built anti-racist approaches to understanding Brazilian racialised and marginalised communities and developed ideas on tropicality that challenged classical European views of an alleged “inferiority” of tropical people and their lands, based on environmental determinism or scientific racism. These anti-racist views of the tropics, which I call “social tropicalism”, acquired international renown thanks to the publications of Brazilian geographer Josué de Castro (1908-1973). Based on new archives and drawing upon recent literature on tropicality and post/decoloniality, I analyse Castro’s early networking with other transnational scholars such as French sociologist Roger Bastide (1898-1974) and Brazilian anthropologist Artur Ramos (1903-1949). Discussing these intellectual exchanges allows for an appreciation of the Brazilian social science “hub” organized around these early universities, and the way they contributed to shape critical scholarly thinking and challenged traditional views on the South as a “tributary” of Northern theories.